Electricity Consumption and Economic Growth: Evidence From Nigeria - Mohammed, Badamasi Sani (Institut Agama Islam Negeri Ponorogo, 2023)
As one of the significant components of energy consumption, the importance of electricity to economic growth has been recognized by economists and business people, engineering, and government agencies. This paper seeks to investigate the impact of electricity consumption on economic growth in Nigeria from 1986 to 2021 by using the Autoregressive Distributed Lag (ARDL) model. The properties of the series were first checked using Augmented Dickey fuller (ADF) and Phillip Peron (PP) unit root tests, and the result found a mixture of the order of integration, which paved the use ARDL model. The findings of the ARDL bond test indicate the present cointegration. Evidence from the short run reveals that the speed of adjustment is negative and statically significant, confirming the expected equilibrium process in the short-run dynamics among the variables under study. The results also show that energy consumption, inflation, and industrial product are statistically significant and positively affect Nigeria's short and long-run economic growth. At the same time, Unemployment is negative and statistically significant both in the short and long run. Based on the findings, the paper recommends that government should undertake serious measures to curtail the shortage of electricity consumption in the country to promote economic growth in general. The government should adopt appropriate policies to reduce Unemployment, adversely affecting economic growth.